Frontier Firms, Technology Diffusion and Public Policy Micro Evidence from OECD Countries - Andrews, Dan (OECD Publishing, 2015)
This paper analyses the characteristics of firms that operate at the global productivity frontier and their relationship with other firms in the economy, focusing on the diffusion of global productivity gains and the policies that faciliate it. Firms at the global productivity frontier - defined as the most productive firms in each two-digit industry across 23 countries - are typically larger, more profitable, younger and more likely to patent and be part of a multinational group than other firms. Despite the slowdown in aggregate productivity, productivity growth at the global frontier remained robust over the 2000s. At the same time, the rising productivity gap between the global frontier and other firms raises key questions about why seemingly non-rival technologies do not diffuse to all firms. The analysis reveals a highly uneven process of technological diffusion, which is consistent with a model whereby global frontier technologies only diffuse to laggards once they are adapted to country-specific circumstances by the most productive firms within each country (i.e. national frontier firms). This motivates an analysis of the sources of differences in the productivity and size of national frontier firms vis-à-vis the global frontier and the catch-up of laggard firms to the national productivity frontier. Econometric analysis suggests that well-designed framework policies can aid productivity diffusion by sharpening firms' incentives for technological adoption and by promoting a market environment that reallocates resources to the most productive firms. There is also a role for R&D tax incentives, business-university R&D collaboration and patent protection but trade-offs emerge which can inform the design of innovation-specific policies
Keywords: Economics